Peran Pendidikan Agama Islam dalam Meningkatkan Kesehatan Mental pada Generasi Z - Nasution, Aqila Khairani; Wahyuni, Sri; Cahaya, Cahaya; Fikri, Muhammad (Universitas Medan Area, 2024)
Optimal mental health is a condition in which an individual's physical, intellectual, and emotional development reaches its peak in harmony with the surrounding environment. Islamic education, as a conscious effort involving teaching, guidance, and care, aims to shape the understanding, appreciation, and implementation of Islamic teachings in everyday life, in accordance with the Qur'an and Hadith. Islam teaches the maintenance of physical and spiritual health through practices such as remembrance (dhikr), fasting, patience, and other concepts. Emphasizing these factors is considered crucial for achieving a healthy life, in line with the guidance of the Qur'an as the foundation of Islamic education.